THE PSYCHOLOGICAL CONTRACT IN A GLOBALIZED SOCIETY: NEW CONTRACTUAL AND RELATIONAL FORMS - AMODIO, Stefano (Economy and Sociology, 2021)
Today, more and more attention is paid to the functioning of organizations, it is placed not only on the work itself, but on the actors and on those subjective dimensions of the worker. In this social-working context the psychological techniques and processes aimed at employment in the new scenario of the globalized society have not yet been studied in all aspects, although its diffusion and importance for the global economy is evident. Also the psychological contract, widely discussed, is an argument with insufficient gaps in scientific research, in particular as regards empirical analysis and theoretical interpretative models. Economic literature has never paid much attention to psychological aspects; on the other hand, psychosocial literature has often omitted use as a specific research topic, focusing on traditional placement and outplacement processes. Some scholars, especially from the Anglo-American school, have emphasized the need to direct research towards an interpretative analysis of the psychological contract based on empirical data, also considering the results of managerial and organizational literature. This article focuses on the process of acquiring and transmitting interpersonal dynamics that characterize the psychological contract with the consequent phases of insertion into the working world, describing its characteristics and its specific dynamics. It also provides an interpretation of these processes, adopting a theoretical model derived from the social psychology of interpersonal relationships. In the end, the article provides some tips to manage the processes of the psychological contract with less stress, psychologically speaking and less organizational uncertainties, mainly addressing the new generations. The purpose of this contribution is to analyze from a psycho-social point of view, the evolution of psychological relationships between employers and workers, within the new scenario of the globalized society, opening new perspectives of investigation and study related to the study of human factors and organizational well-being, work-trust relationships and quality of working preformances.